Hierarchy Of Values In The First Year Students In Connection with The Family Bringing Up Style - Himaieva, Iulia (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2016)
The article contains the research of values’ hierarchy of fist year students girls and boys due to mother’s and father’s bringing up style. It’s revealed that the most signifiant values are hedonism, self-direction and security; Culture Specifi values have the least signifiance. Girls and youths see the prevailing mother’sbringing up style is positive interest, but father’s bringing up styles combines positive interest and autonomy. Correlations between values and family bringing up styles were obtained for girls and boys separately.